Persepsi Audiens Mengenai Konten Iklan Instagram Reels Wardah Matte Lip Cream ‘Tasya Farasya Approved - Khalisa Mecca Medhina (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study aims to determine audience perceptions of the Instagram Reels advertisement content of Wardah Matte Lip Cream "Tasya Farasya Approved" edition. This advertisement is the result of a collaboration between the local cosmetics brand Wardah and the famous beauty influencer Tasya Farasya. This phenomenon is interesting to study considering the trend of influencer-based marketing is increasingly dominant in beauty product promotion strategies, especially in building emotional closeness with consumers and maintaining loyalty to local brands. Consumer perception is an important aspect because it will influence purchasing interest, brand image, and future purchasing decisions. This study uses the perception theory from Jalaludin Rakhmat (2015) which explains that perception is a person's experience of an object or phenomenon obtained through the process of processing, interpreting, and drawing conclusions from the information received. Based on this theory, this study adopted a quantitative descriptive approach. Data were collected by distributing questionnaires to 100 respondents who are followers of Wardah's official Instagram account. Respondents were selected using purposive sampling to ensure the relevance of the data to the research focus. Descriptive data analysis was conducted using SPSS software to identify audience perception patterns regarding advertising content elements, such as visual appeal, message relevance, influencer credibility, and the product image's alignment with Wardah's brand image. This analysis is expected to reveal the extent to which brand and beauty influencer collaborations can create positive perceptions in consumers' minds. The research findings are expected to contribute to the development of digital marketing strategies in the cosmetics industry, particularly in utilizing influencer marketing effectively. Furthermore, the findings of this study can serve as a reference for other local brands in designing promotional campaigns that are relevant, engaging, and aligned with the characteristics of their target audience on social media.